Praktik Jasa Laundry Chesta Barelejo Madiun Perspektif Hukum Islam - Siti Fatimah (Maliyah : Jurnal Hukum Bisnis Islam, 2020)
This is a of field research to highlight on "the Practice of Service of Loundry Chesta Balerejo Madiun" which aims to answer the two fundamental questions: (1) how is the practice of Loundry Chesta Balerejo Madiun? and how is the Review of Islamic Law on Loundry Chesta Balerejo Madiun?. The results of the study concluded that: first, in the practice of Loundry Chesta Balerejo Madiun, consumers came to bring their dirty clothes for laundry, then the dirty clothes were weighed by the laundry owner. The results of the scales and nominal prices were not stated and there was no evidence, either in the form of receipts or notes, so it was only known when the clothes were taken after being washed. In this case, most consumers are willing and do not feel disadvantaged and use the service again; second, the practice of Loundry Chesta Balerejo Madiun above is in accordance with Islamic law because it has fulfilled the pillars and conditions for a valid contract, where the perpetrator of contract is already 'aqil baligh and consists of two people, the object of the contract is clear and known to both parties. As for the case of sighat, although the laundry party did not mention it directly, both parties did not feel aggrieved and mutually agreed to each other. This is allowed by the majority of scholars except for Syafi'iyah scholars.